PRETERMINATION PLANNING. - Silverman, O. Jay (The Accounting Review, 1945)
The government procurement agencies are encouraging their contractors to plan for termination of their war supply contracts in advance. This type of preplanning consists of several methods as advocated by the contracting agencies. Already several agreements have been entered into between the government and the contractors participating, wherein definite and stated terms have been agreed upon by both parties as to how certain problems that will arise at termination will be solved. The writer, being particularly familiar with the textile industry, will attempt to present some of the major problems facing this industry in settling its termination claims. Pretermination studies may seem to be an unnecessary and useless way of spending money, wasting executives' time and tying up personnel. However, an examination of the termination problems affecting the textile industry reveals one factor which alone necessitates these studies the uncertainty of both industry and government as to just what a termination in a textile mill will involve and what fundamental policies of termination will provide the most equitable settlement. Several cardinal points have developed as the result of a study of the worsted industry.